Trask, Lossie. Interview about her life experiences as a volunteer. - Barrett, Terra. (2016)
Oral history interview with Lossie Trask, conducted by Terra Barrett and Sarah Hannon. Interview includes a short life history and a discussion of her involvement with volunteer work. Introduction; Growing up; 1:27 - childhood games; 6:01 beginning volunteering and CGIT (Canadian Girls in Training); describing uniform; church suppers; price of uniforms; 7:45 - talking about Girl Guides; 8:10 discussing her husband’s death and beginning volunteering; 8:45 - talking about the community sector; Senior’s Outreach; Longevity study at MUN; 11:04 - describing CGIT and Girl Guides; 12:45 talking about her children; 13:30 - charity motorcycle rides; 18:50 - talking about her husband’s illness; 20:50 Inuit family heritage; 24:05 - family almanac and heritage; 27:45 - more on volunteering; boys and girls club; 30:10 - family camping trips and games; Terra Nova Park; 34:00 - family albums; 34:49 - describing her music and instruments; 36:35 volunteering.